Project BLING BLING KA-CHING / Suria Sulaiman and Dian Aszyanti Atirah Mohd Asri - Sulaiman, Suria; Mohd Asri, Dian Aszyanti Atirah (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
In the era of challenging economic condition, more students of higher learning institutions are becoming entrepreneurs to increase their sources of income. Some may seek part time jobs in hotels and restaurants just to sustain their life in campus. Several initiatives were introduced to help students cope with their financial hardships. Through Social Entrepreneurship Fund obtained from Universiti Teknologi MARA, Project BLING BLING KA-CHING was introduced. It targeted to students ranging from those categorized as asnaf and zakat recipients who wish to increase their income. Selected students were given skills in sewing beads for scarves and clothing. On 22 July, 2018, 20 students from FPHP and 2 lecturers took part in the project. In the workshop, students were exposed to 6 types of bead stitch, from basic to exclusive bead stitches. Among them is the loop knot beads and pearls, rose sequins. Trained trainers Mrs. Norain Basir was exposing the participants with sewing skills from step by step and at the same time shared on the lucrative income generating opportunities from sewing skills.